Revisiting Barriers to External Finance for SMEs - Ullah, Asad; Bilal, Asad; Hamza, Abdullah; Iqbal, Khalid (Journal of Advanced Research in Business and Management Studies, 2020)
After the Global Financial Crises in 2008, obtaining finance has become more complicated. This study reviews the literature on barriers in accessing external finance given to the importance of availability of finance for all business firms specifically SMEs. Literature over 20 years is searched while reviewing the research question by using Google scholar. Both demand and supply related barriers in accessing external finance has been searched. The study reviewed the factors influencing accessing external finance in the context of developed as well as developing countries with unique conditions and include the issues pre-and post-crises using available literature. The findings of the study discuss the hindrances for SME’s financing mentioned in the literature and highlights the frequently mentioned barriers. Moreover, barriers in accessing external finance in developed and developing countries are different depending upon country environment. It also depends on industry specific effects, firm’s specific effects, and owner’s specific effects. This review provides the problems faced by SME’s in obtaining external finance. Key barriers in accessing finance are also highlighted in the light of available studies. Moreover, it will give further insight to the barriers of small sized firms in developed and developing countries. It has practical value for policy makers while addressing the problem. Future research recommendations will contribute to the literature.